Women in Autophagy: an initiative to promote gender parity in science - McCabe, Mericka; Boya, Patricia; Chen, Ruey-Hwa; Chu, Charleen T.; Colombo, Maria Isabel; Delgui, Laura; Eskelinen, Eeva-Liisa; Hamasaki, Maho; Hansen, Malene; He, Congcong; Jäättelä, Marja; Kimchi, Adi; et al. (NATURE PORTFOLIO, 2025)
Scientific questions are universal but the scientific workforce remains skewed, with women and gender minorities still underrepresented. Initiatives such as the Women in Autophagy network promote the careers of these underrepresented groups with a range of free, year-round scientific, mentoring and networking activities for all scientists.